Antibiotic Overuse in Premature Low Birth Weight Infants in a Developing Country. Issue 3 (March 2019) - Rueda, Maria S.; Calderon-Anyosa, Renzo; Gonzales, Jorge; Turin, Christie G.; Zea-Vera, Alonso; Zegarra, Jaime; Bellomo, Sicilia; Cam, Luis; Castaneda, Anne; Ochoa, Theresa J.
Abstract : Background: Neonatal sepsis is a leading cause of child morbidity and mortality, especially in premature and low birth weight infants. Prompt antibiotic therapy is warranted, but its inappropriate use leads to bacterial resistance and adverse outcomes. Our objective is to describe the antibiotic use for late-onset sepsis in Peruvian premature infants. Methods: This study is a prospective study as a secondary analysis of a clinical trial in 3 neonatal care units in Peru. We included infants in the first 72 hours of life, with birth weight (BW) <2000 g. We described the antibiotic use as length of therapy (LOT) per 1000 patient days (PD) and antibiotic courses. Results: We included 408 neonates, with 12, 204 PD of follow-up; 253 infants (62%) had a BW ⩽1500 g. Total antibiotic use for late-onset sepsis was 2395 LOT (196 LOT/1000 PD). Two-hundred and seventy-one patients (66.4%) did not receive antibiotics for late-onset sepsis during their hospitalization. In total, 204 antibiotic courses were administered; 92 infants (22.5%) received 1 course, and 45 (11.0%) received 2–5 antibiotic courses. Mean duration of antibiotic course was 10.8 days (standard deviation: ±7.3). We found a significant association between a lower BW and increased antibiotic use per day ( P < 0.001). The most commonly used antibiotics were vancomycin (143 LOT/1000 PD), carbapenems (115 LOT/1000 PD), aminoglycosides (72 LOT/1000 PD) and ampicillin (41 LOT/1000 PD). Conclusions: Premature infants receive antibiotics for longer than recommended periods of time. Antibiotic overuse is greater in neonates with lower BW. Vancomycin is the most used antibiotic. There is an urgent need to develop antimicrobial stewardship programs in our setting. Abstract : Supplemental Digital Content is available in the text.